Contribution Linkage and Role of Village Apparatus in Village Finance Management to Achieve Accountability of Village Revenue Expenditure Budget - Mr Karmawan; Dony Yanuar (Fakultas Ekonomi, Universitas Bangka Belitung, 2018)
This Empirical Research aims to look at the contribution and role of Management Village Finance by village apparatus, overall activities including planning, Implementation, administration, reporting and accountability of village finances and Funds Villages sourced from the State Revenue and Expenditure Budget are designated For villages transferred through the District / City Revenue and Expenditure Budget And used to finance the administration, development, Community development, and community empowerment based on Ministerial Regulation Internal Affair of Ministry Number 113 of 2014. The results of this study are expected to contribute to the device Village in district of West Bangka Regency about Strategies to create financial statements and manage a good budget, deliver Training on information technology for village apparatus, training documenting ways and orderly administration and ways of making numbers/codes and codes Documents / archives and others. The population in this study is all of the villages in Mentok and Parit Tiga District of West Bangka Regency while the sample in this study are geographically located villages in Mentok and Parit Tiga Districts of West Bangka Regency. This study uses Primary Data in the form of interviews and Secondary Data taken directly from Object of Research with statistics test. Descriptive and Quantitative Test Correlation (relationship) with Pearson Correlation between research variable.